Analisis Aspek Teknis dan Ekonomis Pemanfaatan Sampah Plastik Polyprophylene Sebagai Alternatif Bahan Bakar : Analysis of Technical and Economic Aspects Utilization of Polyprophylene Plastic Waste as an Alternative Fuel - Ar Rasyid, Fadhil (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
Pekanbaru is the largest city in Riau Province. Pekanbaru has 3 zones of waste transportation, which are combined at the Muara Fajar final disposal site (TPA). The waste at the Muara Fajar TPA consists of organic and inorganic waste, 35% of which is inorganic waste is polyprohylene type plastic waste. The purpose of this study was to analyze the technical aspects and economic aspects of the use of plastic waste as an alternative fuel using the pyrolysis method using the SuperPro Designer software. The results of the research on the technical aspects of the potential of pyrolysis oil produced are 7,769,183 L/year and 23,574 L/day, the electrical energy produced is 186,331 kWh/day. The results of the analysis of economic aspects on the net present value of Rp. 310,503,918,563, for an internal rate of return of 30.24%, and for a payback period of 5 months the return on investment.